Thought Principles in Sherko Bekas's Theatrical Poems - مەجید مەحموود, فازیل; بابەعەلی مستەفا, هیمن (The Scientific Journal of Cihan University– Sulaimaniya, 2024)
Theatrical poetry is one of the four main parts of poetry and forms a significant and large part of the nation's literature. Of course, theatre and theatrical poetry by all nations is based on the stage and situation of the environment at which they have existed and the way of life in which the community and nations are in, has given importance to it and developed. Furthermore, society's awareness has a major and effective role and of great value in this development. Like any other fields of poetry writing, the famous poet Sherko Baska, as of the other areas of poetry has had a great ability and a huge awareness and an important role in writing theatrical poetry, he has written many beautiful texts of theatrical poetry. Especially in the years of early stages of starting of the writing and entering of the world of poetry, like (KAWAI ASNGAR, ASK, DIWAR W DANGY XWEN). In the theatrical texts, there is a high level of thought and content of political, nationalism.